Key players in accountable SDG implementation: National human rights institutions - Anita Breuer; Julia Leininger; Saionara König-Reis (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
Achieving the Sustainable Development Goals (SDGs) of the 2030 Agenda will require strong, accountable institutions. Since no global compliance mechanisms are in place, member states need to establish or use their own institutions and mechanisms to be held accountable for SDG implementation. In July 2021, governments, civil society and the private sector will gather at the annual UN High-level Political Forum on Sustainable Development (HLPF) to take stock of progress on the 17 SDGs. The event provides an opportunity to assess progress made in the establishment of national-level accountability frameworks for the SDGs. Given their legal mandates, national human rights institutions (NHRIs) can play a key role in the implementation and follow-up of the SDGs. However, so far, this role has been scarcely acknowledged by governments in their Voluntary National Reviews (VNRs) on the implementation of the 2030 Agenda.International practice shows that NHRIs play a more active role in providing information for SDG implementation than indicated in the VNRs. For instance, they collect and provide data and build capacities of national institutions. However, NHRIs are rarely represented in national bodies established to oversee SDG implementation. Yet, their ability to support the SDG process increases when they collaborate with the government, get information about SDG policy planning and receive the opportunity to demand explanations about "why" certain policies are adopted and "how" they shall contribute to successful SDG implementation. It is important to note, though, that preconditions for NHRI engagement vary considerably according to country contexts. To strengthen national horizontal accountability in general, and to ensure a human-rights-based approach in implementing the SDGs across all sectors of development, it will be important to: Establish NHRIs that are compliant with the Paris Principles. The pace of progress for establishing NHRIs is too slow. Currently, only half of all countries will achieve SDG indicator 16.a.1 (Existence of independent NHRIs in compliance with the Paris Principles) by 2030. The UN and other international organisations should assist gov-ernments in establishing institutions to be in conformity with the Paris Principles and to enable their effective and independent operation. Ensure an independent voice for NHRIs. Amidst current autocratisation trends worldwide, fundamental freedoms need to be protected. This allows non-state actors and independent state oversight agencies such as NHRIs to criticise government action and demand human rights in SDG implementation. This will also contribute to the direct implementation of SDG target 16.10 on the protection of fundamental freedoms. Enable the participation of NHRIs in national SDG oversight bodies. As a first step, it is necessary that NHRIs themselves raise awareness of their relevant role for better accountability of governments' SDG implementation among national stakeholders. National governments should include NHRIs in the national SDG infrastructure by ensuring their representation in national SDG oversight bodies or government advisory committees. Improve VNR reporting. Governments should make sure to adequately reflect in VNR reporting the role played by NHRIs and assess what they can contribute to national SDG implementation and monitoring.
Keywords: 330